Commodity Terms of Trade : The History of Booms and Busts. (IMF Working Papers; Working Paper ;, 2009)
We compile a historical dataset covering nearly 40 years of booms and busts in the commodity terms of trade of over 150 countries. We discuss the characteristics of these events and their effects on macroeconomic performance and, in particular, compare the most recent commodity-price cycle with its historical precedents.